Intensifikasi Bahasa Arab melalui “Pesantren Kilat Alsun” - Ainun Syarifah (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2017)
Arabic Intensive Program is an Arabic learning program that has been implemented by Madrasah Alsun. The program aims to improve the language competence of the Arabic Teacher Education (PBA) Study Program students whose language competence is still below the standard. PBA study program then cooperated with Madrasah Alsun Sidoarjo to hold Arabic Intensive Program through 'Pesantren Kilat' to improve the Arabic language competence for the students. Pesantren Kilat was held during the two-month semester break. This research used descriptive qualitative research with purposive sampling. The data collection techniques in this study include: Observation, Interview, Documentation, Triangulation and Forum Group Discussion (FGD). The data analysis technique is Interactive Analysis model. In this model, there are three components: data reduction, data presentation, and conclusion or verification. According to the results of the interviews conducted by the researcher, it can be concluded that the success of language learning, including the Arabic language, is not solely related to the competence of the teachers, but actually includes all the components such as capacity of the students, the teaching methods, the supporting media, the learning environments and students’ motivation. Various methods are often used to achieve the effectiveness of learning in the classroom, especially for the students with low Arabic competence